A "Talent Agency" refers children for research: A case study. (June 2022) - Schwebel, David C; Johnston, Anna; McClure, Leslie A
Objective: Ethical standards state research participation must be voluntary and free of coercion and undue influence, but what if a third party appears to engage in research-relevant coercion, without the researchers' knowledge? This case study describes this type of situation and its resolution. Methods: We are engaged in a randomized clinical trial evaluating pedestrian safety with 7- and 8- years old. Depending on children's rate of learning, families receive up to $1275 for their time. We recently learned a third-party "talent agency, " a firm placing children in modeling and acting jobs, was referring families to our research with the expectation that families would share 20% of study reimbursements. Results: We sensed clear impropriety, but identified no ethical violations on our part as researchers. Once paid a study reimbursement, participants can spend funds how they wish. We were concerned, however, that the third-party was exploitatively coercing families to participate. Conclusions: We pursued four avenues to resolve the issue. First, we documented the situation to our university Institutional Review Board. Second, we contacted the talent agency and requested they stop referring families to our research. They agreed. Third, we retained children engaged in our study who were referred from the talent agency; removing them partway through the clinical trial could impact study results. In doing so, we explained that we were unaware of the talent agency referral and that they were not obligated by us to offer a portion of the study reimbursement to the talent agency. Last, we asked newly enrolled families about their referral source.